What is the private return to tertiary education? New evidence from 21 OECD countries - Boarini, Romina (OECD Publishing, 2010)
This article provides estimates of the private Internal Rates of Return to tertiary education for women and men in 21 OECD countries, for the years between 1991 and 2005. IRR are computed by estimating labour market premia on cross-country comparable individual-level data. Labour market premia are then adjusted for fiscal factors and costs of education. We find that returns to an additional year of tertiary education are on average above 8% and vary in a range from 4 to 15% in the countries and in the period under study. IRR are relatively homogenous across genders. Overall, a slightly increasing trend is observed over time. The article discusses various policy levers for shaping individual incentives to invest in tertiary education and provides some illustrative quantification of the impact of policy changes on those incentives
Keywords: Economics